A study of loans advanced by land mortgage banks and their utilisation in Assam - Saikia, Padma Dhar (Ad-hoc study - Agro-Economic Research Centre for North East India ; no. 15., 1969)
Study undertaken at the instance of the Ministry of Cooperation, Govt. of India.